Profil Pemulihan Laju Jantung Orang Terlatih - Adhantoro Rahadyan; Yasmin Tajoedin; Basuni Radi (Jurnal Kardiologi Indonesia, 2008)
Background. A faster recovery of heart rate after exercise has long been associated with higher level of fitness and prognosis. Recent studies have suggested that the rate in which heart rate recovers from exercise or heart rate recovery (HRR) is mediated by autonomic factors, particularly the rate at which vagal tone is reactivated. Several studies were published addressing the diagnostic and prognostic utility of HRR in patients with cardiac disease. This study was to obtain the value of HRR of well-trained men. Methods. It was an observational study that involved well-trained men who underwent medical examination included treadmill stress test in Saryanto Institute of Aerospace Medicine Jakarta.The value of the HRR was defined as the decrease of heart rate from peak exercise to second minute of recovery period. Results. One hundred and twenty eight subjects participated in the study. Thirty five were excluded due to incomplete data. The mean age was 22 ± 1.0 years. Mean heart rate recovery at 2 minutes was 57 ± 10 beat per minute. No different between those with resting heart rate of less than 60 and more than 60 (55 ± 10 vs 58±10 bpm; p:0.1) and amongs different fitness levels (Q1 vs Q4 : 56 ± 11 vs 59 ± 7 bpm, p:0.3)Conclusion. Heart rate recovery at 2 minutes in well-trained men was 57 ± 10 beat per minute.